(untitled) (Nóema, 2011)
The question of order inevitably proposes a reflection aiming at comprehending, from the play between Analytic and Dialectic, the metaphysical significance of the analogical method, the start point being Kant’s logic of relationship. Nevertheless, the tension of the entire categorical arc toward modality leads to refocus the question on the connection among time, space, and possibility.